Explaining economic growth in developed economies after 1980 (2016)
We use the Aguion and Howitt (2009) theoretical model of endogenous economic growth to explain the declining economic growth in developed economies in the period 1981-2009. Aguion and Howitt theoretical framework combines Solownian and Schumpeterian elements in a single scenario, so that labor-augmenting technological progress and capital accumulation per efficiency unit of labor are both caused not only by exogenous changes in the investment rate but also by shocks to the degree of efficiency in the Research and Development (R&D) expenditure process. Empirical results revealed that per worker output growth rates and capital stock per efficiency unit of labor growth rates both have a common panel unit root. Since the panel cointegration tests and estimates revealed a statistical significant negative long-run relationship between per worker output growth rate and capital stock per efficiency unit of labor, the interpretation of the econometric results analized from the Aguion and Howitt ́s theoretical perspective is that labor-augmenting technological progress is endogenously falling over time mainly because of an exogenous deterioration of the environment conditions for the transformation of the investment rate and R&D expenditures in technological progress.